ОРФОЭПИЧЕСКАЯ КОМПЕТЕНЦИЯ: ПОНЯТИЕ, СУЩНОСТЬ, СТРУКТУРА - Саримсакова, Н.К. (SCIENCE and SOCIETY, 2020)
The article actualizes the concept, essence and structure of the orthoepic competence of cadets. The author considers this problem in the framework of the formation of the orthoepic competence of future military personnel. The article substantiates the growing importance of the formation of orthoepic competence, lists the main reasons indicating the need to improve professionally oriented oral speech. The author pays attention to the structure of orthoepic competence of cadets, shows the main possibilities of teaching the discipline «Russian language» for the formation of this competency. The article also presents the methodological means of forming the orthoepic competence of cadets, provides examples of their use. The author substantiates that the formation of the orthoepic competence of cadets at the stage of initial professional self-realization is an important and constant task, since the formation of stable pronunciation standards and the proper level of development of speech culture will ensure the normal functioning of monologic and dialogical oral speech activity in the future.